Simple mathematical models on macrophages and CTL responses against Mycobacterium tuberculosis - Ibargüen-Mondragón, Eduardo; Esteva, Lourdes (Revista SIGMA, 2017)
Resumen En este trabajo se formulan cuatro modelos matemáticos que intentan describir aspectos básicos de la dinámica de la infección con el Micobacterium tuberculosis (Mtb) en diferentes etapas. El propósito de este estudio es evaluar el impacto de la respuesta de las células T y los macrófagos en el control del Mtb. Abstract In this work we formulate fourth mathematical models trying to describe basic aspects into the dynamics of theMycobacterium tuberculosis (Mtb) infection at different stages. The purpose of this study is to evaluate the impact of the response of T cells and macrophages in the control of Mtb.